Homicídio de crianças e adolescentes: análise da psicologia e do direito - Aurichio Junior, Roberto (2018)
The present study deals with Homicide of Children and Adolescents, whose objective was to understand the path of crime, to know why the offender harmed the life of a fetus, newborn, child or adolescent, whether or not son, stepchild and what the relationship is with the victim. If it was by revenge, hatred, neglect, the motivations of the accomplishment or the attempt of the crime. Unfortu- nately, it was intended with the research to contribute in a preventive way to society the necessary vision and direction of forensic psychology, by detecting antisocial conducts to these so vulnerable victims already at an early age, where the families should have the accompaniment of health professionals, education noting the monitoring of children in schools, exploitation, notions of parenting and, if there are physical or emotional maladjustments or signs of aggression, that psychological interventions and consequently of legal operators occur, always with the prevention so that it does not occur the worst, capital punishment, the reason for this research. Method with research design: qualitative and descriptive documentary survey. As a source of data, nine selected cases of crimes against the life of children and adolescents in Curitiba-Pr and Comarcas do Paraná were initially analyzed in the last 10 years, but cases of the 1990s were also located and studied, totaling 1.28% of the cases. 700 cases distributed in the 1st and 2nd Varas of the Jury of Curitiba-Pr. For the analysis of the processes a table was prepared (Annex 1). And, to analyze the psychosocial studies, when they existed, a spreadsheet was prepared (Annex 2). The results demonstrate the vulnerability of the victim in their home environment, absence of vigilance in their daily lives of those who have the duty to watch over, absence of positive parenting styles in the history of aggressors, use of alcohol, drugs, family problems, aggression, low level of schooling, low purchasing power, sometimes not defined profession, complete lack of protection of other family members or acquaintances who could detect these risk factors. It was not intended in this research to exhaust the theme, much has been studied and researched about it, where a more just society is sought, with better relationships and parental styles, consequently and strongly in the prevention of antisocial conducts avoiding crime.